Psychological support for public-funded normal students engaged in teaching profession - Guo, JunRu; Liu, Yu; Chen, YuRong; Chai, GuoLiang; Zhao, XiaoQing (Frontiers in Psychology, 2022)
Among primary and secondary school teachers in China, 70% of teachers believe that they are facing greater occupational pressure. 63.8% of teachers clearly stated that occupational pressure has caused a great or great impact on themselves. And this has had negative effects on them such as mental, physical and personal development. This paper studies the group of public-funded normal students from the perspective of psychological support. This paper uses the SCL-90 form to investigate the professional psychology of teachers for the psychological support of public-funded normal students engaged in the teaching profession. And it conducts a survey on the curriculum setting and satisfaction of the public-funded normal students during their study stage. The experimental results of this paper show that only 11.9% of public-funded normal students are very willing to take root and serve township education. Moreover, the psychological pressure of teachers at different educational stages is quite different.